Nurses’ Individual Characteristics Associated with Five Moments Handwashing Compliance - Maryana Maryana; Rima Berti Anggraini (Jurnal Ners, 2021)
Introduction: The most effective way to control infection is to ensure that hospital staff carry out handwashing according to the protocols. This study aims to determine the characteristics of nursing individuals that affect the compliance of the five moments of handwashing in the hospital inpatient room.Methods: The method used was a quantitative with a cross-sectional approach. The population was all nurses in five inpatient rooms totalling 84 nurses selected using purposive sampling. The dependent variable was the compliance of nurses' handwashing. The independent variableswere the individual characteristics of the nurses, including knowledge, gender, age, attitude, motivation, skin condition, years of service, education, employment status, infrastructure, and type of room. The data were collected using a questionnaire and observation of handwashing compliance. The handwashing observation was based on the hospital guidelines, and the relationship between the variables was analyzed using Chi square and logistic regressions test.Results: The study indicates that there is a significant relationship between motivation, education, and room type on compliance with the five moments handwashing (p <0.05). The most dominant factor was type of room, and there is no relationship between gender, age, years of work, skin condition, knowledge, attitude, employment status and infrastructures (p> 0.05).Conclusion:It is hoped that nurses can increase self-motivation to wash their hands for five minutes while working, as a form of dedication at work and to protect patients and themselves from nosocomial infections. Besides, hospital management needs to make efforts to increase the motivation of nurses.